COLLABORATIVE GOVERNANCE IN ADDRESSING STUNTING IN THE BAJAU COMMUNITY IN BUTON REGENCY - Siradj, Agung Muhammad; Sudarmono, Sudarmono (Jurnal Kebijakan Pemerintahan, 2024)
Abstract This research aims to understand how collaborative governance between the Buton Regency government and other stakeholders related to stunting issues can collaborate and contribute to reducing stunting rates, particularly in the Bajau ethnic community living in the Buton region. Due to their long-standing isolation above the sea, the Bajo/Bajau community has a lower level of welfare compared to other ethnic communities in Buton. Through a descriptive qualitative approach, the researcher found that although collaboration has been effective at the government level, there are still several obstacles, such as suboptimal private sector involvement and low health awareness among the Bajau community. This research can contribute to an approach to governance, especially at the regional level, that prioritizes aspects of collaboration and does not leave the socio-cultural aspects in the community. Keywords: stunting, collaborative approach, Bajau community; local government.